Prenatal, perinatal, and neonatal risk factors of autism spectrum disorder. (August 2018) - Hisle-Gorman, Elizabeth; Susi, Apryl; Stokes, Theophil; Gorman, Gregory; Erdie-Lalena, Christine; Nylund, Cade
Abstract Background We explored the association of 29 previously reported neonatal, perinatal, and prenatal conditions, and exposures with later diagnosis of autism spectrum disorder (ASD) in a large sample of children followed over multiple years. Methods A retrospective case–cohort study was formed using the Military Health System database. Cases were identified by International Classification of Diseases, Ninth Revision codes for ASD between 2000 and 2013, and were matched 3:1 with controls on sex, date of birth, and enrollment time frame. Exposures included 29 conditions previously associated with ASD; 17 prenatal conditions and their pharmaceutical treatment, 5 perinatal conditions, and 6 neonatal conditions. Results A total of 8, 760 children diagnosed with ASD between the ages of 2 and 18 years were matched with 26, 280 controls. ASD is associated with maternal mental illness, epilepsy, obesity, hypertension, diabetes, polycystic ovary syndrome, infection, asthma, assisted fertility, hyperemesis, younger maternal age, labor complications, low birth weight, infant infection, epilepsy, birth asphyxia, and newborn complications. The greatest increased risk was associated with infant epilepsy (odds ratio (OR) 7.57 (5.68–10.07)), maternal mental health (OR 1.80 (1.65–1.96)), and epilepsy (OR 1.60 (1.02–2.50)) medications. Conclusion ASD is associated with a range of prenatal, perinatal, and neonatal factors, with the highest magnitude associations with maternal medication use and neonatal seizure.